2015
DOI: 10.3174/ajnr.a4536
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging in Malignant Brain Tumors: Enhancing the Preoperative Risk Evaluation for Motor Deficits with a Combined Hybrid MRI-PET and Navigated Transcranial Magnetic Stimulation Approach

Abstract: BACKGROUND AND PURPOSE:Motor deficits in patients with brain tumors are caused mainly by irreversible infiltration of the motor network or by indirect mass effects; these deficits are potentially reversible on tumor removal. Here we used a novel multimodal imaging approach consisting of structural, functional, and metabolic neuroimaging to better distinguish these underlying causes in a preoperative setting and determine the predictive value of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…7 Others have shown that TMS mapping that identifies functional tissue in PET-positive lesions correlates with postoperative deficits. 13 Improved methods of preoperative motor mapping are definitely needed, as the currently used DTI tractography has been shown to be poorly sensitive in identifying motor pathways and should always be augmented by direct cortical stimulation. 12 The second major goal of our study was to understand whether intraoperative direct-stimulation motor mapping allowed resection of these classically unresectable tumors with acceptable surgical morbidity and whether the method of mapping, either under general anesthesia or awake motor mapping, influenced extent of resection or morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…7 Others have shown that TMS mapping that identifies functional tissue in PET-positive lesions correlates with postoperative deficits. 13 Improved methods of preoperative motor mapping are definitely needed, as the currently used DTI tractography has been shown to be poorly sensitive in identifying motor pathways and should always be augmented by direct cortical stimulation. 12 The second major goal of our study was to understand whether intraoperative direct-stimulation motor mapping allowed resection of these classically unresectable tumors with acceptable surgical morbidity and whether the method of mapping, either under general anesthesia or awake motor mapping, influenced extent of resection or morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…These radiotracers have been critical in differentiating recurrent enhancing tumour from radionecrosis, a common clinical dilemma in tumour monitoring. It is known that high-grade tumour often lies outside the contrast-enhancing region when using contrast enhanced MR images, and that not all T2 hyperintense tissue surrounding the enhancing component necessarily represents tumour.Recent work combining MR-PET and transcranial magnetic stimulation(Neuschmelting et al, 2016) suggests complementary roles for contrast enhanced MRI and FDG-PET for the identification of areas of eloquent brain that are compromised by tumour, and where resection would be likely to lead to significant deficits. Dynamic studies with FET PET have shown promise in glioma grading, distinction of primary gliomas from metastases, identification of the highest-grade components of tumours (reviewed inMuoio, Giovanella, & Treglia, 2017), and assessment of response to treatment(Albert et al, 2016).…”
mentioning
confidence: 99%
“…able neurological deficits post-surgically. It is known that high-grade tumour often lies outside the contrast-enhancing region when using contrast enhanced MR images, and that not all T2 hyperintense tissue surrounding the enhancing component necessarily represents tumour.Recent work combining MR-PET and transcranial magnetic stimulation(Neuschmelting et al, 2016) suggests complementary roles for contrast enhanced MRI and FDG-PET for the identification of areas of eloquent brain that are compromised by tumour, and where resection would be likely to lead to significant deficits. While much early work in hybrid imaging of brain tumours was done with sequential scans, the increasing use of highly targeted surgical and radio-therapeutic interventions requires the most accurate possible colocalisation of the MRI and PET images; this is most likely to be achieved with simultaneous acquisition, which can also improve the overall diagnostic accuracy of the procedure, as shown by Deuschl et al (2018) with [11-C]-MET-PET-MRI.…”
mentioning
confidence: 99%
“…Neurosurgical tumor resection carries a high risk of unintended brain damage. However, nowadays, preoperative mapping techniques are widely used to avoid injury to eloquent functional cortical regions and the principal white matter tracts that are involved in language processing and movement control [ 6 , 41 , 42 , 43 ]. Moreover, functional reorganization may start early after surgery.…”
Section: Discussionmentioning
confidence: 99%